Out with the Old, in with the New? An Introduction to the Phenomenon of New Churches in Glasgow, Scotland - Akomiah-Conteh, Sheila (Ecclesial Futures, 2021)
The prospects of the church in Britain have been defined by an enduring narrative of regression for many decades, but something new is happening. The presence and influence of old and established institutions are waning, but many new groups are emerging to keep the heritage of the church alive. This quantitative and qualitative study presents the new changes which have occurred in the Christian landscape of the city of Glasgow in Scotland in recent years, which are often hidden from other forms of research such as national church surveys. It reports the formation of 110 new churches in Glasgow between 2000–2016, and the key characteristics and impact of these groups on Christianity in the city. The presence and effect of new churches in Glasgow indicate seismic changes and presents new challenges in the spiritual landscape of this post-Christian city, not least around the homogeneity of the majority of them.